(untitled) (Global Journal of Computer Science and Technology, 2025)
The enhancement of IoT applications for low-power and long-range communication requires the development of communication techniques that consume a small amount of power while transmitting at longer distances LoRa backscatter is a promising solution for such applications In this work we will develop a model that helps to estimate the communication range between a LoRa backscatter tag and a receiver The developed model has been tested by simulation using Python and the results are validated by comparing the achieved range using our model with state-of-art LoRa backscatter works We have also extended the model to account for the effect of SNR loss due to both direct interference from the transmitter and inter-tag interference from neighboring tags in concurrent LoRa backscatter systems